Tata Kelola Pemerintahan Daerah yang Baik dan Pertumbuhan Ekonomi Lokal yang Menimbulkan Pembangunan Daerah :: Haris Faozan 297 Jurnal Ilmu Administrasi Volume VII No. 4 Desember 2010 TATA KELOLA PEMERINTAHAN DAERAH YANG BAIK DAN PERTUMBUHAN EKONOMI LOKAL YANG MENIMBULKAN PEMBANGUNAN DAERAH - Haris Faozan (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2010)
Economic development serves as one of the indicators of success to development. It should be directed to the real and basic economic development at local level, so the economic and social development of a region reaches its goals. The accomplishment of a local government is often linked to the existence of good local governance where there is a synergy between local government,business, and society in governing a region. Good local governance is a concept. Its manifestation is represented in a form of development and public services at local level that truly benefit the majority or whole society. The successes and the failures of development in a region are always linked to the performance of regional apparatus organizations. Because the regional apparatus organizations are always linked with various affairs concerned with local development, it is believed that regional apparatus organizations play vital and strategic roles in development. In relation to that, the regional apparatus organizations must be designed comprehensively and holistically so that the can perform accordingly. It is a high time to avoiding havoc and sporadic management of regional apparatus organizations. It is as well a high time to rectifying this nationwide chaos.